Pengaruh beban pajak, kepemilikan asing dan ukuran perusahaan terhadap penerapan transfer pricing pada perusahaan sub sektor makanan dan minuman yang terdaftar di BEI tahun 2021-2023 - Lakada, Injilita Novitasari; Lambey, Robert; Weku, Priscillia (Yayasan Widyantara Nawasena Raharja, 2025)
This study aims to study the application of transfer pricing schemes in the food and beverage sub-sector of companies listed on the Indonesia Stock Exchange. Transfer pricing is a common practice carried out by multinational companies to shift profits from countries with high tax rates to countries with low tax rates, which can affect the tax burden and overall company performance. The background of this study is based on the significant contribution of the food and beverage sub-sector to Indonesia's economic growth, as well as the large business potential in this sector considering the large population and high purchasing power. This study found several variables that have the potential to influence the application of transfer pricing, namely tax burden, company size, and foreign ownership. The method used in this study is secondary data analysis taken from annual reports published through the Indonesia Stock Exchange (IDX). To analyze the effect of independent variables on the dependent variable, appropriate statistical tests are used. The results of this study are expected to provide deeper insight into the factors that influence the application of transfer pricing in the food and beverage sub-sector of companies, as well as provide recommendations for companies in managing their tax strategies. This study is also expected to contribute to the existing literature on transfer pricing and tax policy in Indonesia.